Usulan Perancangan Sistem Kerja Dengan Metode Macro Ergonomics Analysis and Design (MEAD) pada Stasiun Kerja Percetakan di UD. Roti Rachmat Purwarkarta - Muhammad Ali Akbar; Priyo Ari Wibowo; Ine Indriana Hermawan (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
The rapid advancement of technology today has helped humans in completing their work. Some jobs that require physical activity can still be observed in various types of industrial sectors. Bad impacts can occur if the workload is too heavy and is done repeatedly so that it can affect the health of workers and decrease productivity. UD. Roti Rachmat Purwakarta is a business engaged in the food industry for making bread. The actual condition is that many activities are carried out manually with non-ergonomic working positions. This study aimed to identify and analyze complaints of the musculoskeletal system on the operator and provide suggestions for designing an ergonomic work system. To improve the work system, namely by using the Macroergonomic Analysis and Design (MEAD) method. Complaint identification was carried out using the Standard Nordic Questionnaire (SNQ). The results showed that the pain experienced by the operator at the printing work station was in the left and right shoulders, back, waist, forearms, wrists, knees, and right hands and calves. The result of the REBA score is 10 which indicates the risk levels are high. The results of the proposed work system design are in the form of a hydraulic trolley designed through an anthropometric approach using the 95th percentile so that the dimensions of the worker's body at the printing work station are shoulder width 45.495 cm, maximum grip diameter of 4.735 cm, elbow height 110.752 cm, foot length 25.639 cm and a foot width of 10.510 cm.